Increasing Water Capacity Services for South Binjai Community Demand with Intake Pump - Mahliza Nasution (Kadiri University, 2023)
Indonesia is a country prone to water shortages. Water shortages can affect human well-being and cause disease. This happened in South Binjai Subdistrict, Binjai City, North Sumatra, Indonesia where clean water services were inadequate. Efforts to improve services need to be carried out. This study aimed to evaluate clean water service providers in South Binjai Regency. Evaluation is done by calculating the need for clean water with projected population and customer data. The feasibility analysis of service providers is calculated from the number of people served. So if it does not meet the national standard of 80%, then efforts must be made. The results of the evaluation of service providers in South Binjai District reveal that the coverage of clean water services in 2030 will only reach 17.946%, so service coverage still does not meet national standards. Service providers have limited water capacity. Therefore, the scope of services can be fulfilled by adding operational tools for taking clean water sources such as water pumps. The proposed strategy is to take water from the Bingei River with eight intake pump capacity of 6.25 l/s. The total cost of procuring these pumps in 10 years is IDR 1,529,280,000. Adding the intake pump can increase the water capacity up to 125%. The results of this study can be used as an effort to meet clean water needs in the future.